Simulation of gas-solid flow behaviour in the riser section of a circulating fluidized bed using computational fluid dynamics software - Hussain, A.; Ani, F. N.; Darus, A. N.; Nik, W. B. W.; Mustafa, A.; Salema, A. (2004)
The concept of circulating fluidized bed (CFB) is widely used in industry for catalytic reactions, power production and calcinations of rocks. The gas particle flow inside a CFB unit is very complex. A clear understanding about the hydrodynamics of a CFB can improve the design significantly. CFD modeling of gas particle flow may lead to improved understanding of such system and reduce the need for experimental analysis. A two dimensional and isothermal flow was simulated for the continuous phase (air) and the dispersed phase (solid particles). Conservation equations of mass and momentum for each phase were solved using the finite volume numerical technique. A numerical parametric study was performed on the influence of various physical aspects over the hydrodynamics of gas-solid two-phase flow in a riser. The geometrical configurations of the riser were adopted from of an experimental CFB test rig at the Universiti Teknologi Malaysia, which is still in commissioning phase. A Eulerian continuum formulation was appliedto both phases. A two-dimensional computational fluid dynamics (CFD) model of gas-particle flow in the CFB has been established using the code FLUENT. The computational model was used to simulate the riser over a wide range of 6perating and design parameters. In addition, several numerical experiments were carried out to understand the influence of riser end effects, particle size, gas solid velocity and solid volume fraction on the simulated flow characteristics. Gas and particle flow profiles were obtained for velocity, volume fraction and turbulence parameters for each phase. The computational results were typical of the experimental results reported in literature. Our computational results showed that the inlet and outlet designs have significant effects on the overall gas and solid patterns and cluster formations in the riser. These results were found to be useful in further development of modeling of gas solid flow in the riser.